2015
DOI: 10.1177/0300985815574007
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Periostin in Normal, Atopic, and Nonatopic Chronically Inflamed Canine Skin

Abstract: In humans, periostin plays a critical role in the enhancement and chronicity of allergic skin inflammation; however, whether it is involved in the pathogenesis of canine dermatitis remains unknown. The aim of this study was to examine the expression patterns of periostin in healthy, atopic, and nonatopic chronically inflamed canine skin. Biopsy specimens from 47 dogs with skin disease and normal skin tissue from 5 adult beagles were examined by light microscopy, immunohistochemistry, and in situ hybridization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…We have previously reported that PO expression was more intense in the canine atopic dermis and correlated with the severity of chronic histopathological lesions (epidermal thickening and fibrosis) and CD3+ cell number in the dermis, similar to these reported in hAD patients [ 15 ]. In the article, in situ hybridization (ISH) showed that fibroblasts and keratinocytes were the main source of PO in cAD [ 15 ]. These results suggested that PO may be involved in the pathogenesis of chronicity in cAD.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…We have previously reported that PO expression was more intense in the canine atopic dermis and correlated with the severity of chronic histopathological lesions (epidermal thickening and fibrosis) and CD3+ cell number in the dermis, similar to these reported in hAD patients [ 15 ]. In the article, in situ hybridization (ISH) showed that fibroblasts and keratinocytes were the main source of PO in cAD [ 15 ]. These results suggested that PO may be involved in the pathogenesis of chronicity in cAD.…”
supporting
confidence: 77%
“…Double-ISH for PO and IL-13/ TGF-β1 was performed using the QuantiGene® ViewRNA ISH Tissue Assay (Affymetrix, Santa Clara, CA, U.S.A.) according to the manufacturer’s protocol, as described previously [ 15 ]. Type 1/Fast Red was used for PO probes and Type 6/Fast Blue was applied for IL-13 and TGF-β1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of Postn in skin pathologies (Arima, et al, 2015, Crawford, et al, 2015, Mineshige, et al, 2015, Shiraishi, et al, 2012, Song and Qin, 2008, Supp, et al, 2012, Yamaguchi, et al, 2013, Zhang, et al, 2015, Zhou, et al, 2010) and wound healing (Elliott, et al, 2012a, Elliott, et al, 2012b, Jackson-Boeters, et al, 2009, Nishiyama, et al, 2011, Ontsuka, et al, 2012, Walker, et al, 2015, Zhou, et al, 2010) has been the subject of intense research, which has pointed to very specific roles for Postn.…”
Section: Skin Healingmentioning
confidence: 99%